1977
DOI: 10.1063/1.89471
|View full text |Cite
|
Sign up to set email alerts
|

The photoinduced Rayleigh scattering in BaTiO3 crystals showing the bulk photovoltaic effect

Abstract: In BaTiO3 crystals possessing bulk photovoltaic behavior a photoinduced polarized Rayleigh scattering was observed. The results show that illumination of BaTiO3 crystals creates an inhomogeneous distribution of spontaneous polarization (photofluctuations) which are responsible for both effects, the bulk photovoltaic effect and the polarized Rayleigh scattering. The pseudo-Jahn-Teller effect which was introduced earlier for other photoferroelectric phenomena is assumed to be responsible for the creation of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Since the BPVE tensor is odd, the photovoltaic current should change sign, but with equal magnitude, thereby explaining both the switchability property and that on average, the photovoltaic current in an equally mixed state of up and down domains macroscopically vanishes. Note also that the photovoltaic current vanishes above the Curie temperature in BTO [46,56] and PZT, [57] when spatial inversion symmetry is recovered in the high symmetry paraelectric phase.…”
Section: Reviewmentioning
confidence: 93%
“…Since the BPVE tensor is odd, the photovoltaic current should change sign, but with equal magnitude, thereby explaining both the switchability property and that on average, the photovoltaic current in an equally mixed state of up and down domains macroscopically vanishes. Note also that the photovoltaic current vanishes above the Curie temperature in BTO [46,56] and PZT, [57] when spatial inversion symmetry is recovered in the high symmetry paraelectric phase.…”
Section: Reviewmentioning
confidence: 93%
“…Fundamental understanding of this mechanism is likely to offer new device prospects especially in optoelectronics and information storage . It is to be noted that the photovoltaic effect in ferroelectrics is well known since the 1960s and has been investigated for the optical reading of ferroelectric random‐access memories, photodiodes, and photovoltaic applications. Current research is focused on developing band‐gap tuned ferroelectric materials as their performance is restricted by low mobility of charge carriers and short diffusion lengths .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that doping may also efficiently regulate the properties of BFO, including densities, bandgap, and leakage currents. [68,[81][82][83][84] Xu et al found that the bandgap of BFO could be reduced to 1.1 eV by B-site doping Mn element, as shown in Figure 3a. [85] Ionic substitutions, especially co-substitution of A-site and B-site in perovskite ferroelectric materials are getting more and more popular.…”
Section: Ionic Dopingmentioning
confidence: 97%